READING COMPREHENSION OF REPORT TEXT: THE EFFECT OF OK5R ACTIVITIES THROUGH COOPERATIVE LEARNING (LEARNING TOGETHER) VIEWED FROM READING INTEREST AT XI GRADE STUDENTS OF SMAN 1 RANTAU KOPAR - Eka Melati; Dwi Megista Putri (Universitas Mahaputra Muhammad Yamin, 2019)
This sudy aims at investigating the effect of OK5R (Overview, Key Ideas, Read, Record, Recite, Review and Reflect) activities through Cooperative Learning (Learning Together) on teaching reading of report text viewed from reading interest. This research was a quasi-experimental research by using 2x2 factorial designs.Reading interest was the moderator variable. Population of this research was XI grade students of SMAN 1 RantauKopar. Sample choosed by using cluster random sampling technique: XI IPA was the experimental class and XI IPS 1 was the control one. The instrumentation was questionnanire of reading interest and test of report texts reading.The data analyzed by using t-test and ANAVA for hypothesis testing. The result showed whether: (1) OK5R activities through learning together produced better result on students’ reading comprehension than three-phase strategy; (2) students with high reading interest who are taught by OK5R activities through Cooperative Learning produced better result in reading than those who are taught by Three Phase strategy; (3) students with low reading interest who are taught by OK5R activities through Cooperative Learning produced better result in reading than those who are taught by Three Phase strategy; and (4) there is no interaction between both strategies (OK5R activities through Cooperative Learning and Three Phase strategy) and reading interest toward reading comprehension.OK5R activities through Cooperative Learning was an effective strategy in teaching reading of report texts at senior high school. Students who have high and average reading interest improves their reading comprehension with this strategy. Future research is encoraged exploring the application of this strategy in another kinds of texts as larger population and sample. It was implied that variation strategy used in teaching reading comprehension is important